Teorías de dominio de los docentes sobre el aprendizaje y su expresión en la evaluación de los aprendizajes: un estudio de caso en una institución educativa particular de Lima - Arévalo Alvarado, Rosa María (2010)
This research analyzed what happens when teachers bring curriculum to practice, focusing exclusively in learning assessment, and how in this process their implicit learning theories express themselves. These theories can be: direct, interpretative or constructive, and each one has a tendency to curricular models or teachinglearning approaches like the academicist, interpretative and constructivism. It is considered that teachers tend to some of those theories when expressing their conceptions about learning, and when making decisions. This tendency can be consistent or not with knowledge, daily practice or with institutional guidelines, what is convenient to consider as one of the explaining factors about coherencebetween teachers acting and curriculum.